Analisis Status Mutu Air Sungai Mahakam Kota Samarinda Menggunakan Metode Indeks Pencemaran - Nidya Aulia Nur Annisa; Abdul Hakim; Rr Diah Nugraheni Setyowati (Jurnal Serambi Engineering, 2022)
Sungai Mahakam have an important role in the survival of the surrounding society. Mahakam River is used by the surrounding society for their household needs and also as a source of raw water for Perumdam Tirta Kencana, Samarinda City. In addition, this river is also used for a means of transportation and a lane for barges that carrying coal. This condition allows the pollution that occurs in this river. Physical condition that shows the color of the water is cloudy and the growth of water hyacinth plants along the river. Therefore, the status of the water quality is needed as pollution control for Mahakam River. The method that used to determine the quality status in this study is the Pollution Index. The parameters that used in this study are pH, Temperature, TDS, TSS, COD, BOD and Pb (lead) which were measured according to SNI. The results of the Mahakam River water quality status at point 1-3 are included in the “lightly polluted’ category with 2,106-1,65 value range.